Intraindividual fluctuations in sleep predict subsequent goal setting in adolescents - Laura E. Michaelson; Juliette Berg; Michelle J. Boyd-Brown; Whitney Cade; Dian Yu; G. John Geldhof; Pei-Jung Yang; Paul A. Chase; David Osher; Richard M. Lerner (Journal for Person-Oriented Research, 2022)
The purpose of this study was to investigate within- and between-person associations between sleep and subsequent goal setting in adolescents. We conducted an intensive repeated measures longitudinal study to assess intra- and interindividual associations between sleep and goal setting and potential moderators of such associations. Thirty-nine seventh through 12th graders reported on their sleep quality and propensity to set goals in their daily lives several times per week for approximately four months. We used a combination of multilevel modeling with time-varying covariates and centering techniques to partition within- and between-person variance. We found significant and positive associations between sleep and goal setting within individuals, but no such associations between individuals. That is, students were more likely to set goals for their work after getting a good night’s sleep relative to their own average sleep quality, but getting good sleep on average relative to other individuals showed no association with average goal setting. These relationships were not moderated by participant age, gender, or sociodemographic status as indexed by maternal education. Differences in average sleep between adolescents matters less for their propensity to set goals than whether they experienced better- or worse-than-usual sleep the previous night given their own average. This finding represents the first evidence documenting effects of sleep on goal setting, which is an important psychological precursor to many youth behavioral and achievement outcomes. Our findings highlight the individuality of sleep needs and point to new directions for sleep-related practice and policy aimed at youth.